Variation in the anthocyanin concentration of wild populations of crowberries (Empetrum nigrum L subsp. hermaphroditum) - Koskela, Ali; Anttonen, Mikko; Soininen, Tuula; Saviranta, Niina; Auriola, Seppo; Julkunen-Tiitto, Riitta; Karjalainen, Reijo (Journal of Agricultural and Food Chemistry, 2010)
v 2010 ok puj ksu